Stress and fracture surface analysis of uncoated and coated 7075-T6 specimens under the rotating bending fatigue loading. (May 2020) - Baragetti, S.; Božić, Ž.; Arcieri, E.V.
Highlights: The contribution of the deposition of the DLC coating on the fatigue strength of 7075-T6 is studied. According to the stress field, crack nucleation should be under the surface in the coated samples. Fracture surface observation shows that cracks initiate under the surface in the coated samples. Abstract: The 7075-aluminum alloy is often used in aerospace, automotive, and maritime sectors owing to its high strength-to-weight ratio. Application of Physical Vapor Deposition (PVD) coating has proved to increase tribological properties and corrosion resistance. However, the effects of these coatings on the fatigue strength of coated materials remain to be determined. In this study, rotating bending fatigue tests were performed on uncoated specimens and specimens coated with Diamond-Like Carbon (DLC) in air environment. Total stress was evaluated by the superposition of the bending stress calculated by the finite element method and the residual stress induced by the coating deposition. The superposition of the stress showed that the maximum tensile stress occurs under the specimen surface. Correspondingly, fatigue cracks are expected to nucleate beneath the specimen surface, as confirmed by the observation of the fracture surfaces of the tested samples.